An examination of early New Urbanist developments in the United States: Where are they located and why?. (January 2017) - Song, Yan; Stevens, Mark R.; Gao, Jie; Berke, Philip R.; Chen, Yanping
Abstract: The New Urbanism movement arose in part as a response to adverse societal outcomes associated with sprawl. This article seeks to explain the geographic distribution of the "first wave" of New Urbanist developments in the United States according to three sets of factors: common determinants of residential development, environmental advocacy, and local fiscal and regulatory features. We find that early New Urbanist developments in the United States were supported by jurisdictions with large concentrations of groups that have been supportive of New Urbanism (e.g. environmental non-profit organizations and Democratic voters), although these first wave of New Urbanist developments have received criticism that the environmental promise was not fully realized in practice. We argue that the ability to respond to the criticism with remedies in recent New Urbanism movement will be critical to the eventual success of New Urbanism with respect to evolving into a widespread alternative to sprawl.